2022
DOI: 10.1039/d1mh01539g
|View full text |Cite
|
Sign up to set email alerts
|

Computational design of thermoelectric alloys through optimization of transport and dopability

Abstract: We develop a computational framework to guide the systematic optimization of transport properties and dopability of thermoelectric alloys.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…Therefore, we performed DFT calculations on the SQS ,, of AgMnSnSbTe 4 and AgMnPbSbTe 4 , respectively (Figure ). The absence of the electronic states of the two spin channels at the Fermi level reflects their semiconductor nature.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we performed DFT calculations on the SQS ,, of AgMnSnSbTe 4 and AgMnPbSbTe 4 , respectively (Figure ). The absence of the electronic states of the two spin channels at the Fermi level reflects their semiconductor nature.…”
Section: Resultsmentioning
confidence: 99%
“…We explain the poor p‐type dopability of AgBiSe 2 ‐based materials by calculating the point defect energetics of the end member AgBiSe 2 in the L 1 1 phase using density functional theory (DFT) calculations. In principle, one can examine the formation of point defects in the disordered ABSS alloy using, for example, special quasi‐random structures (SQS); [ 23 ] however, we show that our results of AgBiSe 2 match experimental observations well and provide first‐order insights into the unstable p‐type conductivity in AgBiSe 2 ‐based materials.…”
Section: Resultsmentioning
confidence: 60%
“…Compounds with AM 2 Pn 2 and A 2 MPn 2 stoichiometry illustrate an example of the benefits and drawbacks of this generalized understanding of layered structures . Recent studies have emphasized the importance of cation bonding, identity, disorder, and defects in Yb 2 – x Ca x CdSb 2 , Ca 2 – x Eu x CdSb 2 , Yb 2– x Eu x CdSb 2 , Ca 2– x Lu x CdSb 2 , A 2 CdP 2 (A = Ba, Sr), and AZn 2 Sb 2 (A = Ca, Sr, Yb, Eu) in determining electronic properties and structure type. , In addition, studies on Mg 3 Sb 2 have revealed that the Zintl formalism does not adequately describe interactions between cations and [Mg 2 Sb 2 ] 2– slabs in AMg 2 Pn 2 compounds, which cannot be considered layered structures due to isotropic bonding networks, even though they adopt the CaAl 2 Si 2 structure type. , These examples highlight the need for better understanding of chemical bonding, defects, and local structure in each system to enable optimization of thermoelectric properties.…”
Section: Introductionmentioning
confidence: 99%